2019
DOI: 10.1080/14756366.2019.1609468
|View full text |Cite
|
Sign up to set email alerts
|

A novel anti-platelet aggregation target of chinensinaphthol methyl ether and neojusticin B obtained from Rostellularia procumbens (L.) Nees

Abstract: This study explored the possible bioactive ingredients and target protein of Rostellularia procumbens (L.) Nees. The results of optical turbidimetry revealed that the ethyl acetate extraction obtained from R. procumbens (L.) Nees could inhibit platelet aggregation. Gene chip was used to investigate differentially expressed genes. According to the results of the gene chip, the targets of compounds isolated from the ethyl acetate extraction were predicted by network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Integrin α IIb β 3 is the main receptor regulating platelet aggregation and thrombosis . Previous work done by our group found through the gene chip technology that the extract affected the expression of α IIb β 3 protein on platelets . Thus, it was suggested that the extract had the potential to develop into antiplatelet aggregation drugs.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Integrin α IIb β 3 is the main receptor regulating platelet aggregation and thrombosis . Previous work done by our group found through the gene chip technology that the extract affected the expression of α IIb β 3 protein on platelets . Thus, it was suggested that the extract had the potential to develop into antiplatelet aggregation drugs.…”
Section: Discussionmentioning
confidence: 97%
“…procumbent (L.) Nees is a traditional herbal medicine with the efficacy of detoxicating, activating blood and pain relieving, diuretic swelling, and so on. Previous studies have demonstrated its efficacy in inhibiting platelet aggregation . However, it is not clear if R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, similar to Justicidin A, Justicidin B can selectively inhibit T helper 2 (Th2) cell responses in concanavalin A-activated spleen cells and polarized Th2 cells, thereby alleviating airway inflammation and bronchoconstriction 51 . Justicidin C, also called neojusticin B, has been reported to directly bind to integrin α IIb β 3 to inhibit platelet aggregation 52 . Therefore, based on the results of network analysis and combined with literature reports, justicidin D was used as a key focus in this work for experimental research.…”
Section: Discussionmentioning
confidence: 99%
“…Natural arylnaphthalene lignans and analogs [1,2] continue to interest pharmaceutical industries owing to their biological activities. [3,4] Among them, arylnaphthalene lactones, which are present in a lot of plants often associated with traditional medicine use, are known to exhibit remarkable biological properties, especially antiproliferative, [5][6][7][8][9][10] antiviral, [11] antiplatelet, [12,13] and for this are considered as promising candidates for the elaboration of new drugs. [14] Natural products or analogs included in this family are classified into two types (A or B) related to the regio-orientation of the lactone ring (Figure 1).…”
Section: Introductionmentioning
confidence: 99%